2006
DOI: 10.1128/jvi.80.4.1645-1652.2006
|View full text |Cite
|
Sign up to set email alerts
|

Generation of CD8+T-Cell Responses by a Recombinant NonpathogenicMycobacterium smegmatisVaccine Vector Expressing Human Immunodeficiency Virus Type 1 Env

Abstract: ؉ T cells that were cytolytic and secreted gamma interferon. Effector and memory T lymphocytes were elicited, and repeated immunization generated a stable central memory pool of virusspecific cells. Importantly, preexisting immunity to Mycobacterium bovis BCG had only a marginal effect on the immunogenicity of recombinant M. smegmatis. This mycobacterium may therefore be a useful vaccine vector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 72 publications
2
57
0
Order By: Relevance
“…The SIV env was modified by removing the signal sequence and the gp41 region. The SIV genes were then individually inserted into the multicopy pJH222 Escherichia coli/mycobacterium shuttle plasmid (6). A synthetic operon was constructed containing the viral genes, regulated by the Mycobacterium tuberculosis ␣ antigen promoter and the M. tuberculosis 19-kDa signal sequence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SIV env was modified by removing the signal sequence and the gp41 region. The SIV genes were then individually inserted into the multicopy pJH222 Escherichia coli/mycobacterium shuttle plasmid (6). A synthetic operon was constructed containing the viral genes, regulated by the Mycobacterium tuberculosis ␣ antigen promoter and the M. tuberculosis 19-kDa signal sequence.…”
Section: Methodsmentioning
confidence: 99%
“…ϩ T-cell memory responses in mice, and boosting with rAd5 substantially increased CD8 ϩ T-cell responses specific for that HIV-1 antigen (6,15).…”
mentioning
confidence: 96%
“…In fact, given the extensive clinical experience with BCG, it is being used as a antigen-delivery system for the development of other vaccines. For example, HIV and hepatitis C proteins are being expressed in BCG and other mycobacterial strains [41]. Vaccination of experimental animals with these recombinant BCG strains elicits antigen-specific CD8 + T cell responses [42].…”
Section: Intracellular Bacteriamentioning
confidence: 99%
“…Other non-pathogenic mycobacterial strains have also been considered as vaccines such as the nontuberculous bacteria M. vaccae and M. smegmatis [41,57]. All of these various strains have the potential to elicit both CD4 + and CD8 + T cell responses.…”
Section: Intracellular Bacteriamentioning
confidence: 99%
“…Because of the fact that BCG vaccination has been shown to be safe in newborns, infants, and adults, this bacterium arises as an attractive vaccine vector candidate for recombinant antigens. Indeed, several studies have shown that recombinant BCG strains efficiently induce Th1 responses against several pathogens and diseases (24)(25)(26)(27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%